Count Dracula And The Monster - Jungman, Ann (Collins Educational ltd, 1991)
Many monsters in Victorian British novels were intimately connected with the protagonist, and representative of both a character's personal failings and the failings of the society in which they lived.
Keywords: Juvenile Literature Fiction-Book